Pemetaan Tempat Kos Terdekat dari Universitas Bumigora Menggunakan Metode Location Based Service (LBS) - Ida Laila; Adam Bachtiar Maulachela; Ni Luh Putu Merawati (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Technology has helped many people in providing information to meet their needs. The development of information technology in the field of geography, information can be displayed better and faster through computers, one of which is a geographic information system for mapping the closest boarding house of Universitas Bumigora. The ease of obtaining boarding information is one of the demands in the city of Mataram, especially for migrants, for example students and students, especially STMIK students, Bumigora Mataram, who need temporary shelter. In finding a boarding house, it is sometimes difficult to find the closest boarding house and facilities that fit your needs because you do not know the area, so some boarders have to ask boarding information to the surrounding community or by circling the city which drains energy and costs. Based on these problems, a geographic information system is needed to map the closest boarding house from Universitas Bumigora using the Location Based Service (LBS) method, which is an application to facilitate boarders in finding temporary accommodation without having to search directly to the location. LBS is used to find the geographical position or position of a person through the website. In addition to finding the user's position, LBS can also determine the position of certain places, one of which is a boarding house. LBS is used to lock the search center point of a boarding house, namely Universitas Bumigora and change units to kilometers.